Admiral Gorshkov: the man who challenged the U.S. Navy - Polmar, Norman (Naval Institute Press, 2019)
"The Russian Navy that is at sea in the 21st Century is, to a significant degree, based on the fleet that this man built. This Russian Navy that sent a nuclear-propelled battle cruiser into the Caribbean in 2008, supported the Soviet combat actions in Syria beginning in 2015, and fired missiles from surface ships and a submarine into "rebel" areas in Syria, can trace its "roots" directly to Admiral of the Fleet of the Soviet Union Sergei G. Gorshkov"--